Lithium ion release granules for drinking water, and methods of making and using the same
Patent Information
- Application Number
- CN202611246316.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-09
AI Technical Summary
然而,这类方案存在明显缺陷:天然矿物中锂元素含量分布不均,导致制成的缓释材料中锂离子溶出浓度波动较大,释放寿命难以精确控制和预测;同时,天然矿物中常伴生有铝、铁、锰等金属元素以及铅、镉等重金属元素,在使用过程中易随锂离子一同溶出,污染饮用水,带来健康隐患
[0031]与现有技术相比,本发明至少取得以下有益效果中的一项:
Smart Images

Figure CN122877897A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of drinking water treatment materials technology, and more specifically, to a lithium-ion slow-release granule for drinking water, its preparation method, and its application. Background Technology
[0002] Drinking water is an important way for the human body to obtain minerals. With the improvement of living standards, people's drinking water has gradually shifted from traditional tap water to purified water filtered by water purifiers. However, while water purifiers filter out impurities, they also remove beneficial minerals, and long-term consumption of purified water may affect human health. Lithium, as a trace element beneficial to the human body, can improve learning and memory abilities and reduce the risk of dementia. Therefore, how to safely and stably supplement lithium in drinking water has become an important research direction in the field of drinking water treatment technology.
[0003] Currently, several technical solutions for releasing lithium ions into drinking water have been proposed, mainly including the following categories: In existing technologies, some solutions directly use natural lithium-containing minerals (such as spodumene, lepidolite, and lithium phosphate rock) as lithium source materials, which are then directly or after simple processing for use in drinking water mineralization. For example, the mineralized carbon core in existing post-filter cartridges uses natural spodumene and natural lepidolite to improve the lithium content in the water. However, this type of solution has significant drawbacks: the uneven distribution of lithium content in natural minerals leads to large fluctuations in the lithium ion dissolution concentration in the resulting slow-release material, making it difficult to accurately control and predict the release lifespan; at the same time, natural minerals often contain associated metallic elements such as aluminum, iron, and manganese, as well as heavy metals such as lead and cadmium, which are easily dissolved along with lithium ions during use, polluting drinking water and posing health risks.
[0004] In recent years, slow-release mineralization material technology has been developed. For example, Chinese patent CN117164337B discloses a slow-release mineralization material capable of releasing alkali metal / strontium / selenium elements and its preparation method. The material comprises 4-60 parts of alkali metal / strontium / selenium-containing raw materials, 15-40 parts of silica, 5-10 parts of zeolite, 5-10 parts of quartz, 2-10 parts of binder, and 1-10 parts of nano-silica powder. It is prepared through steps including mixing and slurry preparation, spray granulation, mixing and stirring, molding, sintering, coating, and secondary heating. This material can dissolve only a single mineral element in water, and the content can be controlled within a certain range. Furthermore, Chinese patent CN117164350B discloses a magnesium-rich slow-release mineralization material and its preparation method, comprising 9-50 parts of magnesium-rich mineral raw materials, 15-40 parts of silicon dioxide, 2-10 parts of titanium dioxide, 5-10 parts of zeolite, 5-10 parts of quartz, 5-20 parts of modifier, 2-5 parts of binder, and 1-10 parts of nano-silicon powder. However, these technical solutions mainly target the slow-release of alkali metals (sodium, potassium, etc.), strontium, selenium, or magnesium, and do not specifically propose optimization schemes for the slow-release of lithium ions.
[0005] Chinese patent CN121426271A discloses a method for preparing lithium-ion-rich drinking water and its application. However, this method requires soaking and boiling, and cannot be used for continuous flow processing, making it unsuitable for online use scenarios of conventional drinking water equipment.
[0006] In summary, existing technologies for releasing lithium ions into drinking water still face the following pressing technical challenges: First, existing technologies directly use natural lithium-containing minerals as lithium sources. The uneven distribution of lithium content in the minerals leads to large fluctuations in the concentration of dissolved lithium ions, making it difficult to precisely control the release life.
[0007] Second, while existing slow-release mineralization materials can achieve a certain degree of slow release, they lack precise control over the lithium ion release rate and concentration, making it difficult to flexibly adjust the lithium ion release amount according to different water qualities and usage scenarios.
[0008] Third, metallic elements such as aluminum, iron, and manganese, as well as heavy metals such as lead and cadmium, which are associated with natural minerals, are easily leached out along with lithium ions during use, affecting the safety of drinking water.
[0009] Fourth, some technical solutions require soaking and boiling before use, making them unsuitable for continuous circulation scenarios such as household water purifiers and public drinking water systems. Summary of the Invention
[0010] To address the aforementioned issues, this invention provides lithium-ion slow-release particles for drinking water treatment and a method for preparing the same. The aim is to achieve stable, slow, and uniform release of lithium ions in water while effectively controlling the dissolution of impurities, ensuring drinking water safety, and making it suitable for continuous use in household and public drinking water systems.
[0011] The first aspect of this invention provides lithium-ion slow-release granules for drinking water, wherein the lithium-ion slow-release granules for drinking water comprise, by mass percentage: The composition includes 10%-40% lithium-ion particles, 40%-80% 50-200 mesh magnesium oxide powder, 5%-20% 400-600 mesh magnesium oxide powder, 1%-5% quartz powder, and 4%-15% diatomaceous earth powder.
[0012] Optionally, by weight percentage, lithium-ion slow-release granules for drinking water include: The composition includes 20%-30% lithium-ion particles, 50%-70% 50-200 mesh magnesium oxide powder, 5%-10% 400-600 mesh magnesium oxide powder, 2%-4% quartz powder, and 5%-10% diatomaceous earth powder.
[0013] Optionally, by weight percentage, lithium-ion slow-release granules for drinking water include: 20%-30% lithium-ion granules, 55%-68% 50-200 mesh magnesium oxide powder, 5%-15% 400-600 mesh magnesium oxide powder, 2%-4% quartz powder, and 5%-10% diatomaceous earth powder.
[0014] Optionally, the lithium-ion particles are high-purity lithium oxide or lithium carbonate extracted from at least one of the following natural minerals: lithium phosphate rock, lithium aluminum phosphate rock, lithium manganese phosphate rock, and lithium iron phosphate rock. The purity of lithium oxide or lithium carbonate is 99.5% or higher; Optionally, the 50-200 mesh magnesium oxide powder and the 400-600 mesh magnesium oxide powder are both derived from at least one natural mineral among magnesite, dolomite, and serpentine, which are extracted and purified. The effective content of the components in 50-200 mesh magnesium oxide powder and 400-600 mesh magnesium oxide powder is 98.0% or more.
[0015] Optionally, by weight percentage, lithium-ion slow-release granules for drinking water include: The composition includes 20%-30% lithium-ion particles, 55%-68% 100-200 mesh magnesium oxide powder, 5%-15% 500-600 mesh magnesium oxide powder, 2%-4% quartz powder, and 5%-10% diatomaceous earth powder.
[0016] Optionally, by weight percentage, lithium-ion slow-release granules for drinking water include: The composition includes 20%-30% lithium-ion particles, 55%-68% 100-mesh magnesium oxide powder, 5%-15% 500-mesh magnesium oxide powder, 2%-4% quartz powder, and 5%-10% diatomaceous earth powder.
[0017] Optionally, the quartz powder is quartz powder with a mesh size of 1000-3000. For example, the mesh size of the quartz powder can be any point value or a range between any two points of 1000 mesh, 1500 mesh, 2000 mesh, 2500 mesh or 3000 mesh.
[0018] Optionally, the diatomaceous earth powder is 400-600 mesh diatomaceous earth powder. For example, the mesh size of the diatomaceous earth powder can be any point value or a range between any two points of 400 mesh, 450 mesh, 500 mesh, 550 mesh or 600 mesh.
[0019] In an exemplary embodiment of the present invention, the method for preparing lithium-ion particles includes the following steps: (1) Lithium ore purified material, quartz powder and inorganic silica powder are mixed, silica sol is added to obtain a mixed slurry, and spray granulation is carried out; (2) Calcining the particles obtained by spray granulation; (3) Immerse the calcined particles in a phosphoric acid aqueous solution, dry them, and repeat this step several times; (4) The acid-treated particles are washed and dried sequentially to obtain lithium-ion particles; In step (2), the calcination temperature is 850-950℃. At this calcination temperature, the silica sol is completely dehydrated, condensed, and solidified, and the solid-phase reaction between the powders is achieved. If the calcination temperature is too low, the calcination will be incomplete, resulting in low particle strength. If the calcination temperature is too high, the particles will stick together. For example, the calcination temperature can be any point value or a range between any two points from 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, or 950℃.
[0020] Optionally, in step (3), the concentration of the phosphoric acid aqueous solution is 8-12 wt.%. For example, in step (3), the concentration of the phosphoric acid aqueous solution can be any point value or a range between any two points from 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, or 12 wt.%.
[0021] Optionally, in step (3), the mass of the phosphoric acid aqueous solution is 13-17 wt. of the mass of the calcined particles.
[0022] Optionally, in step (1), by mass fraction, the lithium ore refined material is 55-65 wt.%, quartz powder is 15-25 wt.%, and inorganic silica powder is 15-25 wt.%; Optionally, in step (1), by mass fraction, the lithium ore refined material is 55-60 wt.%, quartz powder is 15-20 wt.%, and inorganic silica powder is 15-20 wt.%; Optionally, in step (1), the concentration of silica sol is 8-12% and the solid content of the mixed slurry is 35-45 wt.%.
[0023] Optionally, the lithium ore refined material is a 300-500 mesh lithium ore refined material powder. For example, the lithium ore refined material can be any point value or a range between any two points from 300 mesh, 350 mesh, 400 mesh, 450 mesh or 500 mesh.
[0024] Optionally, in step (1), the quartz powder has a mesh size of 300-500. Optionally, in step (1), the inorganic silica powder has a mesh size of 500-800. Optionally, in step (1), the particle size obtained by spray granulation is 80-150 mesh.
[0025] Optionally, in step (3), the calcined particles are immersed in an aqueous solution of phosphoric acid, dried, and the step is repeated 2-4 times.
[0026] Optionally, the lithium ore purified material is high-purity lithium oxide or lithium carbonate extracted from at least one natural mineral among lithium phosphate, lithium aluminum phosphate, lithium manganese phosphate, and lithium iron phosphate; the purity of the lithium oxide or lithium carbonate is 99.5% or higher.
[0027] A second aspect of this invention provides a method for preparing lithium-ion sustained-release granules for drinking water, comprising the following steps: S1. Lithium ion particles, 50-200 mesh magnesium oxide powder, 400-600 mesh magnesium oxide powder, quartz powder and diatomaceous earth powder are mixed to obtain a mixture. S2. Add silica sol to the mixture in step S1 and prepare granules by passing it through a sieve; S3. The particles are dried and sieved sequentially to obtain lithium ion slow-release particles for drinking water.
[0028] Optionally, in step S2, the silica sol concentration is 15-25%, and the amount of silica sol added accounts for 30-40 wt.% of the mass of the mixture. Optionally, in step S3, the drying step involves first drying at 100-200℃ and then curing at 250-280℃.
[0029] Optionally, the screening step involves screening out particles of 20-50 mesh.
[0030] A third aspect of the present invention provides the application of lithium-ion slow-release particles in household water purifier filter cartridges, public water dispensers, or centralized drinking water treatment systems.
[0031] Compared with the prior art, the present invention achieves at least one of the following beneficial effects: (1) The present invention utilizes a multi-level porous framework structure constructed by compounding magnesium oxide of different particle sizes, and the synergistic effect of diatomaceous earth pore-forming agent to achieve a slow and uniform lithium ion release rate that can be sustained for several weeks to several months, thus solving the problems of uneven release and unpredictable release life in the prior art.
[0032] (2) The lithium ion slow-release particles prepared by the present invention maintain a lithium ion concentration between 0.13-0.3 mg / L within a water flow range of 2000L, which meets the safety concentration requirements for supplementing lithium in drinking water; and there is no leaching of heavy metal elements such as arsenic, cadmium, chromium, lead, manganese, aluminum, barium, and nickel (below the detection limit), so they are not affected by the quality of the raw ore.
[0033] (3) The granular structure is stable, the water resistance is good, and it is not easy to disintegrate; (4) The raw materials are safe and non-toxic and suitable for drinking water environments. The lithium-ion slow-release particles for drinking water prepared in this application are easy to use. The particles can be directly circulated in water without the need to make carbon rods or additional solubilization and homogenization (microwave) processes.
[0034] (5) The preparation process is simple and the cost is low, making it suitable for large-scale production. Attached Figure Description
[0035] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 An exemplary embodiment of the lithium-ion sustained-release particle product prepared in Example 1 of the present invention is shown; Figure 2 An exemplary embodiment of a flow-through test apparatus diagram is shown. Detailed Implementation
[0036] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0037] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.
[0038] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.
[0039] Example 1 In one exemplary embodiment of the present invention, the lithium-ion slow-release granules for drinking water comprise, by weight percentage: The composition includes 30% lithium-ion particles, 57% 100-mesh magnesium oxide powder, 5% 500-mesh magnesium oxide powder, 3% quartz powder, and 5% diatomaceous earth powder.
[0040] The preparation method includes the following steps: S1: 60 wt.% of 400-mesh lithium carbonate powder (99.7% purity), 20 wt.% of 600-mesh inorganic silica powder, and 20 wt.% of 400-mesh quartz powder were uniformly mixed and then mixed with 10% silica sol. The mixture was spray-granulated to obtain 100-mesh particles. The particles were calcined in a muffle furnace at 900℃ for 3 hours. A 10 wt.% phosphoric acid aqueous solution was prepared and added to the calcined particles (the mass of the phosphoric acid aqueous solution was 15 wt.% of the particle mass). After drying, this step was repeated three times. The particles were washed three times with pure water using a vacuum filter. The lithium-ion particles were obtained by microwave drying.
[0041] Lithium ion particles, 100-mesh magnesium oxide powder, 500-mesh magnesium oxide powder, 2000-mesh quartz powder, and 500-mesh diatomaceous earth powder are placed in a dry material mixer and mixed at 50 rpm for 30 minutes.
[0042] S2. Add silica sol to the mixture at a concentration of 20% and an addition ratio of 35 wt.%, and prepare large particles by passing the mixture through a 20-mesh sieve.
[0043] S3. Dry the large particles in an oven at 150℃, then solidify them in a kiln at 260℃. Sift the particles to 20-50 mesh to obtain lithium-ion slow-release particles for drinking water. (Reference) Figure 1 As shown, Figure 1 A diagram of the lithium-ion sustained-release particle product prepared in this embodiment is shown.
[0044] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles and fill them into a flow-through testing device. (Refer to the flow-through testing device for details.) Figure 2 As shown in Table 1, pure water was used for circulation at a flow rate of 2 L / min, and samples were taken for testing at different cumulative water flow rates.
[0045] Table 1
[0046] Example 2 In one exemplary embodiment of the present invention, the lithium-ion slow-release granules for drinking water comprise, by weight percentage: The composition includes 20% lithium-ion particles, 67% 100-mesh magnesium oxide powder, 5% 500-mesh magnesium oxide powder, 3% quartz powder, and 5% diatomaceous earth powder.
[0047] The preparation method includes the following steps: S1: 55 wt.% of 300-mesh lithium oxide powder with a purity of 99.7%, 25 wt.% of 500-mesh inorganic silica powder, and 20 wt.% of 300-mesh quartz powder were uniformly mixed and then mixed with 10% silica sol. The mixture was spray-granulated to obtain 80-mesh particles. The particles were calcined in a muffle furnace at 850℃ for 3 hours. An 8 wt.% phosphoric acid aqueous solution was prepared and added to the calcined particles (the solution mass was 15 wt.% of the particle mass). The mixture was dried and the process was repeated three times. The particles were washed three times with pure water using a vacuum filtration device. The lithium-ion particles were obtained by microwave drying.
[0048] Lithium ion particles, 100-mesh magnesium oxide powder, 500-mesh magnesium oxide powder, 2000-mesh quartz powder, and 500-mesh diatomaceous earth powder are placed in a dry material mixer and mixed at 50 rpm for 30 minutes.
[0049] S2. Add silica sol to the mixture. The silica sol concentration is 15% and the addition ratio is 30 wt.%. Large particles are prepared by passing the mixture through a 20-mesh sieve.
[0050] S3. Dry the large particles in an oven at 150℃, and then solidify them in a kiln at 260℃. Sieve off particles of 20-50 mesh to obtain lithium-ion slow-release particles for drinking water.
[0051] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates, and the results are shown in Table 2.
[0052] Table 2
[0053] Example 3 In one exemplary embodiment of the present invention, the lithium-ion slow-release granules for drinking water comprise, by weight percentage: The composition includes 20% lithium-ion particles, 57% 100-mesh magnesium oxide powder, 15% 500-mesh magnesium oxide powder, 3% quartz powder, and 5% diatomaceous earth powder.
[0054] The preparation method includes the following steps: S1: 65 wt.% of 500-mesh lithium oxide powder with a purity of 99.7%, 15 wt.% of 500-mesh inorganic silica powder, and 20 wt.% of 300-mesh quartz powder were uniformly mixed and then mixed with 12% silica sol. The mixture was spray-granulated to obtain 150-mesh particles. The particles were calcined in a muffle furnace at 950℃ for 3 hours. A 12 wt.% phosphoric acid aqueous solution was prepared and added to the calcined particles (the solution mass was 15 wt.% of the particle mass). The mixture was dried and the process was repeated three times. The particles were washed three times with pure water using a vacuum filtration device. The lithium-ion particles were obtained by microwave drying.
[0055] Lithium ion particles, 100-mesh magnesium oxide powder, 500-mesh magnesium oxide powder, 2000-mesh quartz powder, and 500-mesh diatomaceous earth powder are placed in a dry material mixer and mixed at 50 rpm for 30 minutes.
[0056] S2. Add silica sol to the mixture. The silica sol concentration is 25% and the addition ratio is 40 wt.%. Large particles are prepared by passing the mixture through a 20-mesh sieve.
[0057] S3. Dry the large particles in an oven at 200℃, and then solidify them in a kiln at 280℃. Sieve off particles of 20-50 mesh to obtain lithium-ion slow-release particles for drinking water.
[0058] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates, and the results are shown in Table 3.
[0059] Table 3
[0060] Comparative Example 1 The main difference from Example 1 is that, by mass percentage, the lithium-ion slow-release particles for drinking water comprise: 15% lithium carbonate and 85% quartz powder. Other preparation steps are the same as in Example 1.
[0061] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates, and the results are shown in Table 4.
[0062] Table 4
[0063] Comparative Example 2 The main difference from Example 1 is that, by mass percentage, the lithium-ion slow-release particles for drinking water comprise: 15% lithium carbonate and 85% zeolite powder. Other preparation steps are the same as in Example 1.
[0064] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates, and the results are shown in Table 5.
[0065] Table 5
[0066] Comparative Example 3 Lithium-ion slow-release granules for drinking water, by weight percentage, include: The mixture contains 20% lithium-ion particles, 57% 100-mesh magnesium oxide powder, 15% 500-mesh magnesium oxide powder, and 3% quartz powder. Diatomaceous earth is not added. The remaining preparation methods and testing conditions are the same as in Example 1.
[0067] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates. The results are shown in Table 6.
[0068] Table 6
[0069] Comparative Example 4 Lithium-ion slow-release granules for drinking water, by weight percentage, include: The mixture contains 20% lithium-ion particles, 77% 500-mesh magnesium oxide powder, and 3% quartz powder. Diatomaceous earth and 100-mesh magnesium oxide are not added. The remaining preparation methods and testing conditions are the same as in Example 1.
[0070] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates. The results are shown in Table 7 below.
[0071] Table 7
[0072] Comparative Example 5 Lithium-ion slow-release granules for drinking water, by weight percentage, include: The mixture contains 20% lithium-ion particles, 77% 100-mesh magnesium oxide powder, and 3% quartz powder. Diatomaceous earth and 500-mesh magnesium oxide are not added. The remaining preparation methods and testing conditions are the same as in Example 1.
[0073] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates. The results are shown in Table 8 below.
[0074] Table 8
[0075] Comparative Example 6 The main difference from Example 1 is that the lithium-ion particles are high-purity lithium carbonate extracted from lithium phosphate ore, with a purity of 99.7%.
[0076] Take 40g of the prepared 20-50 mesh lithium-ion slow-release particles, fill them into a flow-through testing device, and pass them through pure water at a flow rate of 2L / min. Samples were taken and tested at different cumulative water flow rates, and the results are shown in Table 9.
[0077] Table 9
[0078] Test case 20g of the lithium-ion slow-release particles prepared in Example 1 were soaked in 1L of pure water and allowed to stand for 24 hours. The supernatant was then taken to test the heavy metal content. The test results are shown in Table 10.
[0079] Table 10
[0080] Referring to Tables 1-3, the lithium-ion slow-release particles prepared in Examples 1-3 maintained a lithium-ion concentration between 0.13-0.3 mg / L within a 2000L water flow range, meeting the safe concentration requirements for lithium supplementation in drinking water. The particles continued to release effectively even after a 2000L water flow, demonstrating the long-lasting slow-release characteristics of the product of this invention. Referring to Table 10, compared to existing methods that directly use raw ore materials, this application uses high-purity raw materials, resulting in extremely low heavy metal leaching values in the prepared lithium-ion slow-release particles for drinking water during use. Heavy metals such as arsenic, cadmium, chromium, lead, manganese, aluminum, barium, and nickel show no leaching (below the detection limit), eliminating the influence of raw ore quality. Furthermore, the lithium-ion slow-release particles for drinking water prepared in this application are convenient to use; the particles can be directly circulated in water without the need for carbon rods or additional dissolution or homogenization (microwave) processes.
[0081] Comparative Examples 1 and 2 lacked an effective sustained-release framework, resulting in a large amount of lithium ions dissolving in the initial stage, thus failing to achieve sustained release.
[0082] Comparative Example 3 showed poor lithium-ion slow-release performance when diatomaceous earth was lacking.
[0083] In Comparative Example 4, when diatomaceous earth and 100-mesh magnesium oxide were lacking, the fine magnesium oxide particles were too densely packed, which restricted the precipitation of lithium ions and prevented effective slow release.
[0084] In Comparative Example 5, the lack of diatomaceous earth and 500-mesh magnesium oxide resulted in an overly porous framework, leading to a large release of lithium source initially. Subsequently, the release concentration gradually decreased, falling below 0.1 mg / L after 1500 L, indicating insufficient release lifespan.
[0085] Comparative Example 6, without phosphoric acid pretreatment, showed that lithium ions dissolved in large quantities in the initial stage of water contact and were completely consumed after 400L.
[0086] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A lithium-ion slow-release granule for drinking water, characterized in that, By weight percentage, including: The composition includes 10%-40% lithium-ion particles, 40%-80% 50-200 mesh magnesium oxide powder, 5%-20% 400-600 mesh magnesium oxide powder, 1%-5% quartz powder, and 4%-15% diatomaceous earth powder.
2. The lithium-ion slow-release granules for drinking water according to claim 1, characterized in that, By weight percentage, including: The composition includes 20%-30% lithium-ion particles, 55%-68% 50-200 mesh magnesium oxide powder, 5%-15% 400-600 mesh magnesium oxide powder, 2%-4% quartz powder, and 5%-10% diatomaceous earth powder.
3. The lithium-ion slow-release granules for drinking water according to claim 1, characterized in that, The lithium-ion particles are high-purity lithium oxide or lithium carbonate extracted from at least one of the following natural minerals: lithium phosphate ore, lithium aluminum phosphate ore, lithium manganese phosphate ore, and lithium iron phosphate ore. The purity of lithium oxide or lithium carbonate is 99.5% or higher; And / or the 50-200 mesh magnesium oxide powder and 400-600 mesh magnesium oxide powder are both derived from at least one natural mineral among magnesite, dolomite, and serpentine, which are extracted and purified. The effective content of the components in 50-200 mesh magnesium oxide powder and 400-600 mesh magnesium oxide powder is 98.0% or more.
4. The lithium-ion slow-release granules for drinking water according to claim 1, characterized in that, The quartz powder is 1000-3000 mesh quartz powder; And / or the diatomaceous earth powder is 400-600 mesh diatomaceous earth powder.
5. The lithium-ion slow-release granules for drinking water according to claim 1, characterized in that, The preparation method of lithium-ion particles includes the following steps: (1) Lithium ore purified material, quartz powder and inorganic silica powder are mixed, silica sol is added to obtain a mixed slurry, and spray granulation is carried out; (2) Calcining the particles obtained by spray granulation; (3) Immerse the calcined particles in a phosphoric acid aqueous solution, dry them, and repeat this step several times; (4) The acid-treated particles are washed and dried sequentially to obtain lithium-ion particles; In step (2), the calcination temperature is 850-950℃.
6. The lithium-ion slow-release granules for drinking water according to claim 5, characterized in that, The concentration of the phosphoric acid aqueous solution is 8-12 wt.%; And / or, by mass fraction, 55-65 wt.% lithium ore refined feed, 15-25 wt.% quartz powder and 15-25 wt.% inorganic silica powder; The concentration of the sol and / or silica sol is 8-12%, and the solid content of the mixed slurry is 35-45 wt.%.
7. The lithium-ion slow-release granules for drinking water according to claim 5, characterized in that, The lithium ore purification material is 300-500 mesh lithium ore purification powder; And / or the quartz powder has a mesh size of 300-500; And / or the inorganic silica gel powder has a mesh size of 500-800; The particle size obtained by spray granulation is 80-150 mesh.
8. A method for preparing lithium-ion slow-release granules for drinking water as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Lithium ion particles, 50-200 mesh magnesium oxide powder, 400-600 mesh magnesium oxide powder, quartz powder and diatomaceous earth powder are mixed to obtain a mixture. S2. Add silica sol to the mixture in step S1 and prepare granules by passing it through a sieve; S3. The particles are dried and sieved sequentially to obtain lithium ion slow-release particles for drinking water.
9. The preparation method according to claim 8, characterized in that, In step S2, the silica sol concentration is 15-25%, and the amount of silica sol added accounts for 30-40 wt.% of the mass of the mixture. And / or in step S3, the drying step is to first dry at 100-200℃ and then cure at 250-280℃.
10. The application of lithium-ion slow-release particles as described in any one of claims 1-7 in household water purifier filter cartridges, public water dispensers, or centralized drinking water treatment systems.
Citation Information
Patent Citations
A slow-release mineralization material capable of dissolving alkali metals / strontium / selenium elements and a preparation method thereof
CN117164337B
A magnesium-rich slow-release mineralized material and preparation method thereof
CN117164350B
Preparation method and application of lithium ion-rich drinking water
CN121426271A